RELASI AKAL DAN AGAMA DALAM - Damanik, Nur Liana (UIN Sumatera Utara Medan, 2019)
Intellect as the power of thought that exists in humanity strives to close at God and revelation as a message from the realm of metaphysics down to humans. Religion is a kind of regulation that avoids humans from chaos and delivers humanity to order. In the Indian intellectual tradition, Darsana is a philosophical (western) term, but essentially, there are very basic differences, (western) philosophy apart from religion while darsana remains rooted in religion. This study explains how the relationship between philosophy and religion using the library reset approach. The knife of analysis is used. The primary books are related to philosophy, religion, and Hindu teachings, in finding the truth through the study above. Philosophy in Hindu religion is known as Sad Darsana. Hindu philosophy (darsana) is a process of rationalization of religion and is an integral part of Hinduism that cannot be separated. Religion provides the practical aspects of ritual and darsana provides aspects of philosophy.